Dissemination of Sharia Cooperative Research, Solutions during a Pandemic - Riduwan Riduwan; Farid Ma’ruf (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The COVID-19 pandemic has hurt various business sectors, including Indonesian Retired Migrant Entrepreneurs (PMI), in Yogyakarta. Many of the tourism, culinary, and small trade sectors are directly affected, as PMI's business base, causing new, increasingly complex problems such as running out of capital, difficulty in marketing, and weakening enthusiasm for the business. Sharia Cooperative Training as community service, providing new enlightenment and confidence for PMI members in redeveloping their business through Sharia-based cooperatives. With an adult or participatory training approach, participants gain further understanding and enthusiasm. Through Sharia cooperatives as an economic movement based on kinship and cooperation, cooperative members can strengthen and help each other. The training results show that PMI members agree to create a Sharia Cooperative that provides capital, joint marketing of member products, and increasing business capacity. Sharia cooperatives were chosen because they are more in line with beliefs and, in principle, are more suitable for the pandemic because of the applied profit-sharing system.